Mathematical Reasoning of Class VII Students in terms of Mathematical Resilience in TAI Learning with the RME Approach Aided by Graphic Organizer - Chusna, Cahya Amalia; Rochmad, Rochmad; Zaenuri, Zaenuri (Universitas Negeri Semarang, 2021)
This study aims to describe students' mathematical reasoning abilities of grade VII based on mathematical resilience in TAI learning with the RME approach assisted by a graphic organizer. The research method used in this study is a mix method with sequential explanatory models. The population in this study were students of class VII MTs Ma'arif 1 Blora academic year 2020/2021 with a sample of class VII C and class VII B as the experimental class and the control class. The research subjects were two students each with high mathematical resilience, moderate mathematical resilience, and low mathematical resilience. The data collection techniques used in this study were tests, documentation, questionnaires, observations, questionnaires, and interviews. The quantitative data were tested by means of the average test, the proportion test, the average difference test and the different proportions test, while the qualitative data were tested with data validity, data reduction, data presentation and conclusion mean The results showed that students in the high mathematical resilience category were able to master all indicators of mathematical reasoning. Students in the mathematical resilience category are less able to make and test mathematical guesses. Students in the mathematical resilience category are unable to make and test mathematical guesses, perform mathematical manipulations and draw conclusions from a statement or fact logically.